PEMANENAN AIR HUJAN PADA PERUMAHAN (REAL ESTATE) MELALUI PEMBANGUNAN DANAU DALAM RANGKA MENGURANGI EKSPLOITASI AIR TANAH DAN LIMPASAN AIR KE DRAINASE DI KOTA MALANG - Galih Damar Pandulu; Esti Widodo (BUANA SAINS, 2015)
Open space in the form of a lake to infiltration as well as a rainfall harvesting on housing (real estate) ranging from home and residential area to address the water needs are increasing along with the development of the growing city of Malang. The purpose of this study was to use excess of rainfall the rainy season an area of residential real estate that does not cause rainfall runoff into the environment outside the housing area. Research methods used to determine the topography of the study area and the proportion of land use in the form of a green open space and space awakened. Hydrological analysis includes frequency analysis of rainfall, rainfall intensity calculations certain return period, and discharge plans. The results of this study is the volume of water that can be accommodated on a residential scale. With existing discharge on Sukun Pondok Indah housing at 4,48 m3/sec in an open area and 41.59 m3/sec in the region woke up and discharge a total of 46.07 m3/sec. For a rainy day for 60 minutes to come by volume of 165,865.53 m3 of water. Housing Buring Permai for a rainy day for 60 minutes to come by water volume of 556,059.14 m3, Housing Permata Jingga for a rainy day for 60 minutes to come by water volume of 106,484.48 m3, Housing Ijen Nirvana for a rainy day for 60 minutes to come by water volume of 330,820.57 m3